Importance of dental care to maintain oral health of children and youth with type 1 diabetes - Anna Kuźmiuk; Grażyna Marczuk-Kolada; Elżbieta Łuczaj-Cepowicz; Marta Obidzińska; Ewa Chorzewska; Urszula Wasilczuk; Anna Kierklo; Sławomir Dariusz Szajda (Nofer Institute of Occupational Medicine, 2018)
Background Dental care for children and youth with type 1 diabetes should rely on reliable examination of the oral cavity, early treatment of dental caries and maintenance of the treatment results. This can be achieved through regular control visits consistent with the standards, and also through following the recommendations for prevention of dental caries and periodontal disease. The aim of the study was to investigate whether dental care allows to preserve good oral health of children and youth with type 1 diabetes. Material and Methods The study included 60 patients with type 1 diabetes, aged 7-17 years, and 30 healthy children and youth within the same age range. There were evaluated intensity of caries, the effectiveness of conservative treatment, periodontal health and oral hygiene. Results The results of examinations showed significantly lower caries prevalence and better periodontal health in the children and youth with type 1 diabetes. The effectiveness of conservative treatment was significantly higher among patients with mixed dentition. There was no significant difference in oral hygiene between the compared groups. Conclusions Diabetes is a risk factor for oral diseases, so children and youth with type 1 diabetes should be provided with special preventive care and curative measures. The main goal of the insulin-dependent diabetes care program is to early classify them to highrisk groups to improve general oral health and thus improve the quality of life. Proper dental care for children and yuoth with type 1 diabetes is a condition to maintain oral health. Med Pr 2018;69(1):37-44